Revision of the Nearctic Microphorinae (Diptera: Dolichopodidae sensu lato) - Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2022)
The Nearctic species of the dolichopodid subfamily Microphorinae are revised. Two genera and 33 species are recognized including five species of Microphor Macquart and 28 species of Schistostoma Becker. Both genera are redefined, redescribed and diagnosed, a key to the genera and species in the Nearctic Region is provided, the known geographical distribution of each species is mapped and ecological information is summarized. In addition to the three previously known species of Nearctic Schistostoma, i.e., S. armipes (Melander), S. sycophantor (Melander) and S. yakimense (Melander), the Nearctic fauna includes eight species newly transferred from Microphor as well as 17 new species. These species of Schistostoma are classified into four species groups as follows: the S. atratum species group including S. atratum (Coquillett, 1900) comb. nov., S. borkenti sp. nov., S. chloeae sp. nov. and S. lillyae sp. nov.; the S. isommatum species group including S. caroleae sp. nov., S. evisceratum (Melander, 1940b) comb. nov., S. fitzgeraldi sp. nov., S. isommatum (Melander, 1928) comb. nov., S. powelli sp. nov., S. shamshevi sp. nov., S. sinclairi sp. nov., S. susanae sp. nov. and S. tacomae (Melander, 1940b) comb. nov.; the S. ravidum species group including S. armipes (Melander, 1928), S. arnaudi sp. nov., S. cirripes (Melander, 1940b) comb. nov., S. heatherae sp. nov., S. longistylum sp. nov., S. michaeli sp. nov., S. oharai sp. nov., S. ravidum (Coquillett, 1895) comb. nov., S. robustum (Melander, 1928) comb. nov., S. rudei sp. nov., S. strigilifer (Melander, 1940b) comb. nov. and S. sycophantor (Melander, 1902); and the S. yakimense species group including S. pecki sp. nov., S. runyoni sp. nov. and S. yakimense (Melander, 1928). Schistostoma ravum (Melander, 1940b) comb. nov. is also transferred from Microphor and is newly synonymized with S. evisceratum (Melander, 1940b), syn. nov. The Nearctic members of Microphor now comprise only three of the previously known species, plus two new species. These five species are classified into two species groups as follows: the M. discalis species group including M. discalis Melander, 1940b, M. skevingtoni sp. nov. and M. turneri sp. nov.; and the M. obscurus species group including M. bilineatus (Melander, 1902) and M. obscurus Coquillett, 1903. Lectotype designations are made for Holoclera bilineata Melander, Microphorus armipes Melander, Microphorus ravidus Coquillett, Microphorus strigilifer Melander and Holoclera sycophantor Melander.